Marketing innovation for higher education a bibliometric analysis using the VOS viewer application - Khairusy, Mirza Abdi; Gaffar, Vanessa; Karsikah, Karsikah; Suprayogi, Yogi; Ardie Putra, Alfian Prayana; Haryadi, Didit (Jurnal Mantik, 2024)
The purpose of this research is to carry out a bibliometric analysis of marketing innovation in higher education using VOSviewer. This study uses a quantitative description method. The data used in this study are search results based on the keyword "Marketing Innovation" sourced from Google Scholar using publish or perish software. The search results found 981 articles published between 2018-2022. The results of the research show that research on marketing innovation has decreased in 2018-2022. In conclusion, this research needs to be carried out to show the importance of conducting bibliometric analysis, especially in the field of marketing innovation. It is hoped that this research can become a reference for further research in conducting and determining research themes, especially on the theme of marketing innovation. This research is expected to contribute theoretically to the literature in the context of marketing management